HUBUNGAN KEMAMPUAN KERJA DAN ANGKA MANGKIR KERJA KARYAWAN HOTEL BINTANG TIGA BAGIAN HOUSEKEEPING DI DENPASAR - Prasetio, Renaldi; Adiputra, Nyoman (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic); Vol 2 No 1 (2016): Volume 2 No 1 Juni 2016DO - 10.24843/JEI.2016.v02.i01.p02)
The work ability of employees and work absence is important in nowday's. These things need to be considered to achieve good service quality, especially the hotel employees at housekeeping department. Employees task at housekeeping department is very important, especially for the comfort and cleanliness of the hotel. The employees with good workability and low work absence will certainly improve the quality of service of the hotel. The purpose of the research was to find out the correlation between work ability and work absence among 3-star hotel employees at housekeeping department at Denpasar. This research was using a cross-sectional analytic study. The number of respondents were 31 people consisting of 3-star hotel employees at housekeeping department atDenpasar. The  respondents were asked to fill Work Ability Index and mention work absence in the past year. Tables are used to show the results of the study and analyzed using the Spearman correlation test.  The research showed that the average of work ability is 41.48, sickness absence and off work are 3.74 and 11.22. There was significant correlation between work ability andnumber of a sickness absence (p=0.006). While the work ability and number off work have no correlation (p=0.461). It can be concluded that work ability and sickness absence have a correlation but there was no correlation between work ability and off work among 3-star hotel employeesat housekeeping section.  It may suggest  to  implementing  regular training to improve employability in an effort to decrease sickness absence
Keywords: Work Ability, Work Absence, Sickness Absence, Off Work